Hukum Kekayaan Intelektual Dalam Mendukung Inovasi Bisnis Di Era Digital - Putri, Amanda; Aulia Marsha; Farren Qhuntum Khaira; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2024)
Intellectual property law (IP law) plays a crucial role in supporting business innovation in the digital age. With the rapid advancement of technology and globalization, IP protection becomes increasingly important to prevent piracy, trademark infringement, and copyright violations that can harm innovators and companies. This paper aims to analyze how IP law can facilitate business innovation by protecting copyrights, trademarks, patents, and industrial designs, as well as addressing challenges in the digital era. IP law provides legal guarantees that protect intellectual creations from unauthorized use, which can enhance a company’s competitiveness and drive economic growth. The study will also discuss the issues faced in implementing IP law, such as copyright violations, trademark imitation, and difficulties in enforcing IP law violations. With a deeper understanding of IP law, companies can develop more effective strategies to protect their works and ensure that intellectual property rights are respected in the global market. In this context, IP law not only serves as a legal tool but also as a catalyst for innovation, providing incentives for companies to invest in research and development of new products. In the fast-paced digital era, IP protection also helps create a fairer ecosystem for innovators by ensuring that their works are not misused by irresponsible parties